Conflict resolution of grammar and gender for avian species-group names under Article 31.2.2 of the ICZN Code: is gender agreement worth it? - Schodde, Richard; Bock, Walter (Zootaxa, 2016)
We analyze recent nomenclatural treatment of selected avian species-group names that may be either adjective and variable or noun and invariable. In 27 such names, we found that 14 previously identified as adjectives are nouns under Article 31.2.2 of the International Code of Zoological Nomenclature. Five of them may require correction in current checklists; they are bresilius in Ramphocelus bresilius (Linnaeus, 1766) to bresilia, germana in Amblyornis macgregoriae germana Rothschild, 1910 to germanus, argentinus in Muscisaxicola cinereus argentinus Hellmayr, 1932 to argentina, martinicus in Porphyrio martinicus (Linnaeus, 1766) to martinica, and moluccus in Threskiornis moluccus (Cuvier, 1829) to molucca. Mindful of the compounding effect of species-genus recombination from taxonomic revision, we reach the conclusion, not new, that the requirement for gender agreement in species-group names is the single biggest cause of nomenclatural instability in zoology. To resolve it, we support replacing gender agreement by original spellings for species-group names.